I Am Malala : The Girl Who Stood Up for Education and was Shot by the Taliban (Old) - Malala Yousafzai; Christina Lamb (London, United Kingdom Orion Publishing Co, 2014)
d
Keywords: Autobiographies -- Autobiographies; Biographies -- Biographies